Penyuluhan dan Praktik Pengelolaan Pascapanen Tanaman Obat di Plalangan Gunungpati Semarang: The Socialization and Practice of Post-harvest Management for Medicinal Plants at Plalangan Gunungpati Semarang - Mulangsri, Dewi Andini Kunti; Hidayati, Devi Nisa; Puspitasari, Anita Dwi; Rahmatun, Mutia; Pasha, Salsabilla Putri Buana; Fikriyyah, Shafa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Post-harvest management is essential because it will affect the final results. Post-harvest management products can be classified as simplicia because the stages include wet sorting, washing, draining, changing shape, drying, packaging, and storage. These steps must be paid attention to to ensure the content of active compounds in simplicia. The Bejo Bintang Toedjoe herbal garden at the Plalangan Gunungpati sub-district is managed by women from the Plalangan sub-district, both housewives and workers. Community service was implemented by preparing and making leaflets/brochures, conducting site surveys, conducting pretests and posttests, and monitoring and evaluating the practical results. This activity was attended by 25 participants, not only participants from the managers of the Bejo Bintang Toedjoe herbal garden but also residents from representatives of several community associations. The discussion session was opened after the counseling had been delivered. After the discussion session is finished, it continues with practice. The results of the pretest analysis showed that most participants still need to learn the effect of direct heating with sunlight for drying medicinal plant materials. Some participants also needed to learn that the tools used to cut medicinal plant materials were stainless steel. The posttest results showed that there was an increase in knowledge after conducting counseling and post-harvest management practices of medicinal plants.